Salivary MMP-8, MAF, and IL-34 levels in non-surgical periodontal treatment of gingivitis patients - DOĞAN, BAŞAK (My University, 2022)
Background and Aim: Specific biomarkers' diagnostic ability for peri-odontitis has been identified and widely studied; however, such stud-ies targeting gingivitis are rather rare. The aim of the study was toevaluate the levels of matrix metalloproteinase (MMP-8), Interleukin(IL)-34, and macrophage activating factor (MAF) in the saliva of peri-odontally healthy and gingivitis participants and to compare thechanges following non-surgical periodontal treatment (NSPT) Methods: A total of 36 subjects, 18 periodontally healthy and 18 gingi-vitis, were recruited to the study. The clinical periodontal parameterswere recorded, and the saliva samples were collected from all subjectsat baseline. Gingivitis patients received NSPT, and all clinical peri-odontal parameters and saliva samples were re-collected at 3 months.MMP-8, MAF, and IL-34 levels were analyzed by using ELISA. Thisstudy was supported by grants from Marmara University ScientificResearch Projects Coordination Unit #SAG-A-230119-0014.Results: All clinical parameters were higher in the gingivitis group thanthe healthy ones at baseline and improved at 3 months after NSPT ingingivitis patients (p< 0.05). Salivary MMP-8 and IL-34 levels weresignificantly higher in gingivitis patients compared to healthy ones atbaseline (p< 0.05). The salivary MMP-8 levels in the gingivitis groupdecreased at 3 months compared to baseline (p=0.008). However,salivary IL-34 levels remained unchanged throughout the study period(p> 0.05). The salivary MAF levels were similar between gingivitis andhealthy groups at baseline (p> 0.05), whereas significantly decreasedat 3 months compared to baseline (p=0.002).Conclusions: The results of this study confirm that salivary MMP-8plays a role as a reliable biological marker in the pathogenesis of gingi-vitis, and NSPT is effective in decreasing its levels. In addition, peri-odontal inflammation was found to alter salivary IL-34 levels ingingivitis patients